HUBUNGAN TINGKAT KEBISINGAN PESAWAT UDARA TERHADAP KESEHATAN PEKERJA DI SEKITAR LANDAS PACU 1 DAN 2 BANDAR UDARA INTERNASIONAL SOEKARNO–HATTA, BANTEN - Sintorini, Margareta Maria; Hutapea, Paido H.; Vicaksono, Agrivickona Ario (Jurnal Teknologi Lingkungan Universitas Trisakti, 2007)
The Relations between Airplane's Noise Level and Employees Health in Runways 1 and 2 Soekarno-Hatta International Airport, Banten. Soekarno-Hatta International Airport in Tangerang, Indonesia has flew over 70.000 passengers every day nowadays, it has 2 runways with specification number 07R/25L, length 3600 m (1st runway), 3660 m (2nd runway), width 60 m and can be used for Boeing 747 landing. Noise level measurement at Soekarno-Hatta International Airport conducted at 4 measurement points around 1st and 2nd runway using Sound Level Meter at 300 m from runway. 120 questionnaires were given to the employees around runway to observe their health problem. The result of noise level measurement was due from 72,15 dB(A) to 87,93 dB(A).As for Time Weighted Average (TWA) calculation was only conducted at point 1 to point 4, but point 1 and point 2 was not included at the calculation due to normal result at point 1 and 2 compared to the permitted threshold 85 dB(A) which ruled by Kep - 51/MEN/1999. As for point 3 and 4 the result shown that Time Weighted Average are 88,40 dB(A) and 88,52 dB(A) for 5,48 hours and 5,33 hours. The result shown that 41,67 % of employees at PKP-PK unit had hearing problem, as for office employees is 3,33 %. The result shown that Self Protection Device was the only significant relation due to employeesâ€™ hearing problem with 1,5 times larger hearing problem chance to the employees with more than 10 years work duration compared to the less than 10 years work duration employee. As for the official workers the risk was 4,1 times for the employees with more than 50 years old age compared to less than 50 years old age. Self Protection Device usage should be more effective with regular inspection by the occupational safety authorities and punishment to the indiscipline employee, and to place more barriers at the location which has direct impact to the employees, and also placing some acoustic noise absorber at PKP-PK building.Â Abstract in Bahasa Indonesia:Bandar Udara Internasional Soekarno-Hatta adalah bandar udara terbesar di Indonesia yang saat ini menerbangkan 70.000 orang tiap harinya, spesifikasi panjang landasan pacu (runway) 1 dengan nomor 07R/25L sebesar 3600 m dan runway 2 dengan nomor 07L/25R sebesar 3660 m dan lebar 60 m. Pengukuran bising dilakukan di 4 titik di sekitar wilayah runway 1 dan 2 menggunakan alat Sound Level Meter (SLM) pada jarak 300 m dari runway. Untuk mengetahui keluhan yang dialami oleh pekerja di area runway dilakukan penyebaran kuesioner terhadap pekerja sebanyak 120 buah, 20 eksemplar pada tiap unit PKP-PK, serta 60 pada area perkantoran. Hasil pengukuran antara 72,15 dB(A) sampai 87,93 dB(A). Perhitungan tingkat pemaparan kebisingan (TWA) dilakukan pada titik 1 hingga 4, adapun titik 1 dan 2 tidak dilanjutkan karena masih dibawah ambang batas yaitu 85 dB(A) oleh Kep- 51/MEN/1999. Perhitungan TWA di titik 3 dan 4 menunjukkan waktu pemaparan yang diizinkan sebesar 5,48 jam dan 5,33 jam, pemaparan sebesar 88,40 dB(A) dan 88,52 dB(A). Dari penyebaran kuesioner didapat hasil sebanyak 41,67 % pekerja di unit PKP-PK mengalami gangguan pendengaran, dan di area perkantoran sebanyak 3,33 %. Berdasarkan analisis statistik diketahui bahwa kepatuhan terhadap penggunaan alat pelindung diri (APD) memiliki hubungan yang bermakna terhadap gangguan pendengaran pekerja di unit PKP-PK dengan masa kerja >10 tahun memiliki resiko 1,5 kali mengalami gangguan pendengaran dibanding masa kerja < 10 tahun. Pekerja di perkantoran dengan umur > 50 tahun memiliki resiko 4,1 kali lebih besar mengalami gangguan pendengaran dibanding pekerja dengan umur < 50 tahun. Efektifitas penggunaan APD sebaiknya ditingkatkan dengan pemeriksaan berkala oleh pihak K3 PT. Angkasa Pura II serta pemberian sanksi bagi yang melanggar, begitu pula dengan pemberian barrier pada daerah yang berhubungan langsung dengan lokasi kerja serta pemberian peredam akustik pada bangunan PKP-PK.